2017
DOI: 10.1111/rda.13102
|View full text |Cite
|
Sign up to set email alerts
|

Polo‐like kinase 1 inhibition results in misaligned chromosomes and aberrant spindles in porcine oocytes during the first meiotic division

Abstract: Polo-like kinase 1 (Plk1), a type of serine/threonine protein kinase, has been implicated in various functions in the regulation of mitotic processes. However, these kinase's roles in meiotic division are not fully understood, particularly in the meiotic maturation of porcine oocytes. In this study, the expression and spatiotemporal localization of Plk1 were initially assessed in the meiotic process of pig oocytes by utilizing Western blotting with immunofluorescent staining combined with confocal microscopy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
(37 reference statements)
1
5
0
Order By: Relevance
“…Similar to work assessing the role of PLK1 in oocytes using siRNA and kinase inhibition approaches, we demonstrated that PLK1 is required for spindle integrity to ensure the formation of normal bipolar spindles capable of facilitating chromosome segregation during meiosis I ( Clift and Schuh, 2015 ; Solc et al. , 2015 ; Liao et al. , 2018 ).…”
Section: Discussionsupporting
confidence: 64%
“…Similar to work assessing the role of PLK1 in oocytes using siRNA and kinase inhibition approaches, we demonstrated that PLK1 is required for spindle integrity to ensure the formation of normal bipolar spindles capable of facilitating chromosome segregation during meiosis I ( Clift and Schuh, 2015 ; Solc et al. , 2015 ; Liao et al. , 2018 ).…”
Section: Discussionsupporting
confidence: 64%
“…PLK1 and SKA1 are two newly discovered genes associated with mitosis and tumorigenesis. PLK1 encodes a serine/threonine protein kinase, which is a critical regulator of cell cycle progression, cytokinesis, mitosis and the DNA damage response (40). The deletion of the PLK1 protein dramatically inhibited cancer cell proliferation and induced apoptosis (41).…”
Section: Discussionmentioning
confidence: 99%
“…The accurate segregation of genetic information between daughter cells are the most fundamental processes of life and requires a molecular machine built primarily of microtubules that form a specialized bipolar‐shaped spindle to drive the congression of chromosomes at metaphase I (M I) stage and the segregation of chromosomes at anaphase I (A I) stage in cells 21‐24 . Thus, the precise spatiotemporal coordination of spindle assembly and chromosome alignment is essential for the orderly progression of oocyte maturation 25 . Any mistake during this process is prone to chromosome segregation errors that would result in the aneuploid eggs 26 .…”
Section: Introductionmentioning
confidence: 99%